2013
DOI: 10.1007/s00592-013-0532-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel enzyme-linked immunosorbent assay for bivalent ZnT8 autoantibodies

Abstract: Autoantibodies to zinc transporter 8 (ZnT8A) is a powerful diagnostic or predictive marker in type 1 diabetes. However, the widely used current ZnT8A radioligand binding assay (RBA) has proved to be difficult for many laboratories to implement. The aim of this study was the development and characterization of the performance of a novel fluid phase ZnT8A enzyme-linked immunosorbent assay (ELISA) in relation to standard radioligand binding assay (RBA) in type 1 diabetes. Sera from 114 patients with type 1 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…As the bridging‐type ELISA for ZnT8A used in the present study would be easy to implement and has proven to achieve a high degree of sensitivity and specificity in the recent proficiency evaluations by the Islet Autoantibody Standardization Program, this assay should be deemed a useful diagnostic method for determining type 1 diabetes. Although the provided cut‐off value for this kit (ElisaRSR™ ZnT8 Ab) by the manufacturer is <15 U/mL 6 , we have established a distinctive cut‐off value of <10 U/mL for Japanese populations based on the 99th percentile and 3SD above the mean value obtained through the 288 healthy Japanese control participants. Although the exact reasons for the cut‐off difference between Japanese people and white people are unknown, one possibility might be attributed to the effect of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the bridging‐type ELISA for ZnT8A used in the present study would be easy to implement and has proven to achieve a high degree of sensitivity and specificity in the recent proficiency evaluations by the Islet Autoantibody Standardization Program, this assay should be deemed a useful diagnostic method for determining type 1 diabetes. Although the provided cut‐off value for this kit (ElisaRSR™ ZnT8 Ab) by the manufacturer is <15 U/mL 6 , we have established a distinctive cut‐off value of <10 U/mL for Japanese populations based on the 99th percentile and 3SD above the mean value obtained through the 288 healthy Japanese control participants. Although the exact reasons for the cut‐off difference between Japanese people and white people are unknown, one possibility might be attributed to the effect of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…ZnT8A, GADA and IA‐2A were determined using bivalent ELISA kits (RSR Ltd., Cardiff, UK) using biotinylated ZnT8, GAD65 and IA‐2, respectively, as described previously 6,11,12 . All of these determinations were based on the sandwich type principle with dimeric carboxy‐terminal domains of ZnT8 (aa 275–369) carrying either 325Trp or 325Arg, full‐length GAD65 and intracellular domain of IA‐2 (aa 604–979) as antigens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure the diversity of the screened scFv, we chose ZnT8 N/C fusion protein for bio-panning. Since previous studies showed that principal epitopes targeted by ZnT8A were influenced by a single amino acid at position 325 encoded as arginine or tryptophan in T1D, the ZnT8 C terminal dimer with Arg325Trp mutation protein has been proved to possess both specificity and sensitivity to detect ZnT8A (Kawasaki et al, 2014;Kawasaki et al, 2008;Wenzlau et al, 2008). We identified the specificity of scFvs through ZnT8 C terminal dimer with Arg325Trp mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamic decarboxylase‐65 autoantibodies titers were measured by the RIA and ELISA, with cut‐off values of 1.5 and 5.0 U/mL, respectively. Titers of IA‐2A and ZnT‐8A were measured by RIA, with a cut‐off value of 0.4 U/mL (range 0.4–50 U/mL), and by ELISA, with a cut‐off value of 15 U/mL (range 15–2000 U/mL), respectively. If the IA‐2A and ZnT‐8A titers fell below the lower limits of detection, a fill value of 0.01 was used.…”
Section: Methodsmentioning
confidence: 99%